GABA-A Receptor Modulation and Anticonvulsant, Anxiolytic, and Antidepressant Activities of Constituents from Artemisia indica Linn. (7th April 2016) - Khan, Imran; Karim, Nasiara; Ahmad, Waqar; Abdelhalim, Abeer; Chebib, Mary
Abstract : Artemisia indica, also known as "Mugwort, " has been widely used in traditional medicines. However, few studies have investigated the effects of nonvolatile components of Artemisia indica on central nervous system's function. Fractionation of Artemisia indica led to the isolation of carnosol, ursolic acid, and oleanolic acid which were evaluated for their effects on GABA-A receptors in electrophysiological studies in Xenopus oocytes and were subsequently investigated in mouse models of acute toxicity, convulsions (pentylenetetrazole induced seizures), depression (tail suspension and forced swim tests), and anxiety (elevated plus maze and light/dark box paradigms). Carnosol, ursolic acid, and oleanolic acid were found to be positive modulators of α 1 β 2 γ 2L GABA-A receptors and the modulation was antagonized by flumazenil. Carnosol, ursolic acid, and oleanolic acid were found to be devoid of any signs of acute toxicity (50–200 mg/kg) but elicited anticonvulsant, antidepressant, and anxiolytic activities. Thus carnosol, ursolic acid, and oleanolic acid demonstrated CNS activity in mouse models of anticonvulsant, antidepressant, and anxiolysis. The anxiolytic activity of all three compounds was ameliorated by flumazenil suggesting a mode of action via the benzodiazepine binding site of GABA-A receptors.